PENGARUH KOMPENSASI, KEPEMIMPINAN TRANSFORMASIONAL, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - Fathimining Ayu Puspitasari; Idayanti Nursyamsi; Wahda Rasjid (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Employees as one of the spearheads of service providers directly to BPJS Employment Participants, is expected to have high performance. This study aims to examine the effects of compensation, transformational leadership and organizational commitment to employee performance through job satisfaction. Population in this research is all employee BPJS Employment Branch of Makassar. The sampling technique used is to use non probability sampling with saturated sampling method. With a sample size of 97 employees. Data analysis using Partial Least Suares (PLS) analysis. The research findings show that 1) Compensation has a negative and significant effect on employee performance. 2) Transformational leadership has a positive and insignificant impact on employee performance. 3) Organizational commitment has a positive and significant impact on employee performance. 4) Job satisfaction has positive and insignificant effect on employee performance. 5) Compensation has negative and insignificant effect on employee performance through job satisfaction. 6) Transformational leadership has a positive and significant effect on employee performance through job satisfaction. 7) Organizational commitment has a positive and significant impact on employee performance through job satisfaction. Of the three variables only organizational commitment that has influence on employee performance with job satisfaction as intervening variable.